FENOMENA SILENT READER DALAM GRUP WHATSAPP: STUDI FENOMENOLOGI PADA BARISTA KOPI KENANGAN KARAWANG - Dewi, Ghina Kartika; Ramdhani, Muhamad; Arindawati, Weni A (Program Studi Ilmu Komunikasi Universitas Komputer Indonesia, 2021)
The widespread use of Whatsapp in everyday modern human life’s who communicate without being limited by space and time.. This is because Whatsapp offers the ability to send messanges and create a whatsapp group chat that useful for spreading information practically with just one click, the massive use of the Whatsapp group chat feauter on. In Whatsapp group chat there is an admin who can invite and remove members in whatsapp chat group. And there are active members who always provide theire opinion or spread information, besides that there are also member of Whatsapp group chat who are passive even though theire as member of group chat Whatsapp. And it’s called Silent Reader. Silent reader doesn’t theire respon. So that communicator doesn’t get a feedback of the information that’s been spread in whatsappp group chat. This research aims to find out how someone in using Whatsapp group chat that can become as a silent reader. This research uses qualitative descriptive method, with data collection techniques, namely interviews with 5 informants in whatsapp chat group Barista Kopi Kenangan Karawang Yogya branch. The results of this study indicate that a personn’s can act as a silent reader in Whatsapp group chat are about theire Selectivity, Involment and theire needs. Keywords: Whatsapp Group Chat, Feedback, Silent Reader